The sun and photovoltaic technologies - Pavlovic,Tomislav (Cham,Switzerland: Springer, 2020)
This book covers solar energy and the use of solar radiation in connection with lighting. It provides a detailed introduction to solar energy, photovoltaic (PV) solar energy conversion, and solar lighting technologies, while also discussing all of these elements in the context of the Balkan Peninsula. In the context of solar energy, the book covers a range of elements, from the structure of the sun, to PV solar plants. It subsequently addresses the status quo of solar technologies in Bulgaria, Serbia and the Republika Srpska and analyses the development of these technologies over the years, including their economic status, and how these aspects have shaped their current status. Undergraduate and graduate students, researchers and professionals, particularly those based in the Balkans, will find this book both informative and interesting.
Includes index.
Keywords: Lighting; Photovoltaic power generation; Solar cells